Metaphor in the Lyrics of A Javanese Folk Song Entitled Lir-Ilir By Sunan Kali Jaga - Salsabila, Fara Adiba; Marwan, Iwan; Sakina, Vanesa Audria (Literature Research Journal, 2024)
This research aims to reveal the metaphors present in the song Lir Ilir. Accurately and clearly capturing semantic information is crucial for students to fulfill their tasks and responsibilities in accordance with linguistic ethics and norms. This study is qualitative in nature and employs a semantic approach. The listening technique was used for data collection, while the data analysis was conducted using the matching method. The findings indicate that the song Lir Ilir serves as a medium for passing down cultural values, traditions, advice, and daily habits, all of which reflect local wisdom. The message is conveyed through metaphorical language that sounds aesthetically pleasing yet carries deep meaning when fully understood. The metaphors found in the song can be classified into anthropomorphic metaphors, metaphors from concrete to abstract, and synesthetic metaphors. These elements reflect cultural teachings, including gratitude for God's blessings, encouragement for socialization, humility, motivation to make the most of youth and time, as well as advice to remain vigilant in life.Metafora dalam Lirik Lagu Rakyat Jawa Berjudul Lir-Ilir Oleh Sunan Kali JagaPenelitian ini bertujuan mengungkap metafora dalam lagu Lir Ilir. Menangkap informasi semantik dengan jelas dan akurat sangat penting bagi peserta didik untuk memenuhi tugas dan kewajibannya sesuai dengan etika dan kaidah kebahasaan. Penelitian ini termasuk kualitatif dan menggunakan pendekatan semantik. Teknik simak digunakan dalam pengumpulan data. Selain itu, untuk menganalisis data menggunakan metode padan. Hasil penelitian menunjukkan bahwa lagu Lir-Ilir berfungsi sebagai media untuk mewariskan nilai-nilai budaya, adat istiadat, nasihat, dan kebiasaan sehari-hari yang menunjukkan kearifan lokal. Pesannya disampaikan melalui bahasa metaforis yang terdengar indah namun memiliki makna yang dalam jika dipahami. Metafora yang terdapat dalam lagu dapat dibedakan menjadi metafora antropomorfik, metafora konkrit ke abstrak, dan metafora sinestetik. Hal tersebut mencerminkan ajaran budaya, antara lain rasa syukur atas karunia Tuhan, dorongan untuk bersosialisasi, kerendahan hati, motivasi untuk memanfaatkan masa muda dan waktu sebaik-baiknya, serta nasihat untuk tetap waspada dalam hidup.